Qualidade de vida no trabalho de professores de instituições federais de ensino superior: um estudo em duas universidades brasileiras - Paula, Alessandro Vinicius de (2015)
This exploratory, descriptive and multicase research aimed at analyzing the perceptions of Quality of Work Life (QWL) higher teaching of teachers from two Brazilian federal universities: Federal University of Mato Grosso (UFMT) and Federal Technological University of Paraná (UTFPR). The study included 715 teachers, 428 from UFMT and 287 from UTFPR. We evaluated the following factors and indicators of QWL: meaning of work and meaning at work; psychological suffering; psychological well-being; work-related stress; work-life balance; working hours (daily/weekly) and workloads. We considered a qualitative and quantitative approach to the development of this study, dividing the data collection into three stages: a) documentary research; b) electronic questionnaire application (online survey) and c) conducting focus groups. We noted that in the studied federal universities, the precariousness is associated with three main elements, which we defined as a university teaching work randomization tripod - formed by: the academic productivism; excessive bureaucratic activities and administrative work; and inadequate working conditions. This tripod has a harmful effect over the health of teachers and their work quality. Considering workplace relations, we found that, for our participants, contact with students is configured as a source of pleasure/fulfillment, while interpersonal relationships with teaching colleagues appeared as a complicating factor in conducting their work. Other obstacles faced by teachers in their daily work-life regard difficulties in balancing a personal life with work demands and inadequate conditions for the work development. Analyzing these results allowed us to understand the physical and mental elements that strain the analyzed teachers and the precarious context in which they live. Such strain have committed to Quality of Life in the investigated group of teachers in order to make it difficult for these workers to find meaning in their work. We hope this study can subsidize intervention programs and public health promotion for university teachers, enabling the creation of better strategies to improve human resources management policy within higher education federal institutions. Such actions are necessary in building a university committed to the health of the community.